Sharia accounting on Indonesian Financial Accounting Standard on zakat and waqf take on industrial revolution 4.0 and society era 5.0 - Arwani, Agus (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - The aims to point out the challenges and expectations towards sharia accounting profession on zakat and waqf in facing the industrial revolution.Method - This research used a qualitative approach by systematically explaining various sources of literature. Â Result - The results of the research shows that the era of the Industrial Revolution 4.0 and Society 5.0 offers convenience and speed, making people turn into super fast and human-centered. Both professional and sharia accountants need a pattern of self-management on the basic functions of sharia accounting which will, in turn, increase the efficiency and effectiveness of their work and the results can be shown in real-time.Implication - Research implication shows that some companies have developed this because of the support gained from the adequate standardization of financial management processes and standardization information systems architecture and by the demands of the fourth-generation industry proving that crucial competencies are needed for sharia accountants of zakat and waqf.Originality - The research shows that Islamic accountants must understand Indonesian Financial Accounting Standard 109 on Zakat, Infaq and Sadaqah, and Indonesian Financial Accounting Standard 112 on Waqf which is based on information technology in the era of Industrial Revolution 4.0 and Society Era 5.0.